First Record of Cardiocondyla obscurior Wheeler, 1929 (Hymenoptera: Formicidae: Myrmicinae) for Pakistan - Majeed, Waqar; Koch, Elmo Borges A.; Rana, Naureen; Naseem, Rimsha (Sociobiology, 2021)
Ants of the genus Cardiocondyla are considered omnivorous in nature. This genus is native to Afrotropical, Australasia, Indomalaya, Malagasy, Oceania, and Palearctic regions. A total of 72 valid species and 2 valid subspecies has been described worldwide. However, little is known about these ants in Pakistan. As a result of a survey of different sites in the Gatwala park of district Faisalabad during 2018, we collected individuals of the genus Cardiocondyla. Collected specimens were identified using the most recent and available literature. Prior to current work, only two species of this genus were reported for Pakistan. In this study we added the first record of Cardiocondyla obscurior for Pakistan, followed by a brief description, distribution, and identification key.